NMC510 : Animation production / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course is designed to expose students to the basic techniques and skills in creating a 3D animated film through the production pipeline. The principal purpose of this course is to help develop the skills of students in the various stages within the production pipeline of preparation and production of an animated programme or film. Students will learn through the whole production pipeline from the beginning of an idea in pre-production till the final product is completed in post-production. Students will also learn through the process of the 3-production phase within the context of animation. This is a practical course in animation production that involves learning and developing skills in the various stages of producing an animated programme or film.